Peran Guru dalam Meningkatkan Keterampilan Berfikir Kritis Siswa Melalui Model Pembelajaran Berbasis Masalah di SD Negeri 01 Trans Bangsa Negara - Sholihin, Muhammad Irfani; Hasim, Wahid (LPPPI Publishing, 2025)
This study aims to examine the role of teachers in improving the critical thinking skills of fifth-grade students at SD Negeri 01 Trans Bangsa Negara through a problem-based learning model. This study used a qualitative approach with a case study design. Data were collected through classroom observations, teacher interviews, and document analysis, including lesson plans. The results showed that although the problem-based learning model was proven to encourage students to think critically in a more varied way, the level of students' critical thinking abilities was generally still classified as moderate.